2000
DOI: 10.1111/j.1151-2916.2000.tb01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure Formation in the Combustion Synthesis of Al2O3–TiC Composites

Abstract: Structure formation in the combustion synthesis of Al 2 O 3 -TiC composites from TiO 2 , Al, and graphite powders was investigated using cylindrical samples and cone-shaped "quenching samples." It is shown that the phases Ti and Ti 3 Al exist as intermediates in the combustion synthesis process. Titanium carbide forms in a secondary step through reactions between graphite and liquid Ti or Ti 3 Al, then nucleates from a liquid mixture of the three phases Ti, Ti 3 Al, and alumina. The nucleated particles grow in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 18 publications
(23 reference statements)
0
14
0
1
Order By: Relevance
“…Thus, the microstructural evolution could be observed and analyzed by scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS). The microstructural transitions of TiC-Fe [7], Al 2 O 3 -TiC [8] and NiAl [9] have been observed by using the combustion front quenching method (CFQM). In this paper, the synthesis mechanism of Mg 2 Ni from powders by self-propagating combustion was studied using CFQM.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the microstructural evolution could be observed and analyzed by scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS). The microstructural transitions of TiC-Fe [7], Al 2 O 3 -TiC [8] and NiAl [9] have been observed by using the combustion front quenching method (CFQM). In this paper, the synthesis mechanism of Mg 2 Ni from powders by self-propagating combustion was studied using CFQM.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the reactions in the preheated region could be described by the following equations: The irreversible transformation of anatase to rutile (Eq. [3]) takes place at approximately 918 K. [11] The formation of TiB 2 through the reductive reaction of TiO 2 with B 4 C has been testified by some researchers. [27][28][29] With the increase in temperature as the SHS reaction progressed, the titanium oxides further reacted with Al into the formation of Al 3 Ti, which could be expressed as…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…[4] In the past decades, extensive research has been carried out on the SHS reactions in Al-TiO 2 -C and Al-TiO 2 -B 2 O 3 systems for producing (TiC-Al 2 O 3 )/Al and (TiB 2 -Al 2 O 3 )/Al composites. [5][6][7][8][9][10][11][12][13][14][15] Unfortunately, the research on the SHS reaction in the Al-TiO 2 -B 4 C system was relatively rare. Only recently, Wang et al [16] reported the preparation of an Al-matrix composite reinforced by multiphases of ceramics, a-Al 2 O 3 -TiCTiB 2 , through the combustion reaction in a 55.6 wt pct Al-36 wt pct TiO 2 -8.4 wt pct B 4 C sample in a molten Al (~1100°C) environment.…”
Section: Introductionmentioning
confidence: 99%
“…represent a new class of materials with improved mechanical properties, hardness and wear resistance when compared to monolithic ceramics [1][2][3][4][5][6][7]. AT composites are widely used as substrate of magnetic heads and cutting tools due to their attractive mechanical properties and good electrical conductivity [8]. At present commercially available micro-sized AT composites are prepared by pressure-less sintering or hot pressing the direct mixtures of Al 2 O 3 and TiC powders [9,10] during which severe grain coarsening and generation of metal oxides at the interface always take place due to relatively long holding time at high temperature [11].…”
Section: Introductionmentioning
confidence: 99%